Pandangan Gereja Katolik atas Realitas Kawin Lari di Stasi Santa Odilia Balohili Simanaere Paroki Salib Suci Nias Barat - Blasius Superma Yese; Mawarni Gea; Elisman Boy Gulo (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2024)
The research entitled, "The View of the Catholic Church on the reality of Elopement at the Santa Odilia Balohili Simanaere Station of the Holy Cross Parish of West Nias" intends to find out the reality of eloping at the Santa Odilia Balohili Simanaere Station, West Nias Holy Cross Parish. Marriage is a lifelong alliance between a man and a woman in forming a family. However marriage cannot always be carried out by someone. Some of these marriages were held because they did not get the consent of their parents and because the dowry/honesty was so large. The reality today is that there are many marriages or marriages that are held outside the authority of the Catholic Church, such as underage marriages, elopements, and secret marriages that are only recognized by government law. This study intends to explain and describe the main reasons why members of the Santa Odilia Balohili Simanaere Stasi made the decision to elope in forming a new family.